Assistance in the Development of Digital Marketing for Ecotourism through Social Media at Curug Cilember - Yati Yati; Fitra Jaya; Kadarisman Kadarisman; Romi Siswanto; Gayatri Oktalina; Agnisa Widyanti (Jurnal Pengabdian UNDIKMA, 2026)
This community service activity aims to strengthen the capacity of Curug Cilember tourism managers to utilize social media as a creative and informative promotional tool capable of reaching a wider market. Through a participatory approach and technical training, lecturers and students from Universitas Terbuka provided intensive assistance covering visual content creation, social media account management, digital storytelling techniques, and promotional campaign evaluation. The results of the program demonstrate an increase in participants’ understanding and skills, particularly in designing attractive visual communication strategies aligned with the natural tourism characteristics of Curug Cilember. In addition, the activity raised participants’ awareness of the importance of digital branding in the management of community-based tourism destinations. Supported by grant funding and close collaboration between academics and the local community, this initiative is expected to expand Curug Cilember’s promotional reach to national and international audiences and contribute to increased tourist visitation as well as improved economic welfare of the surrounding community.